PENGARUH MOTIVASI BELAJAR, DISIPLIN BELAJAR DAN MEDIA PEMBELAJARAN TERHADAP KESIAPAN BELAJAR SISWA KELAS X ADMINISTRASI PERKANTORAN PADA MATA DIKLAT MENGELOLA PERALATAN KANTOR DI SMK NU 01 KENDAL - Yanida, Ayu Fitria; Pramusinto, Hengky (Economic Education Analysis Journal, 2014)
Tujuan penelitian ini adalah untuk mengetahui Pengaruh motivasi belajar, disiplin belajar dan media pembelajaran terhadap kesiapan belajar siswa kelas X administrasi perkantoran pada mata diklat mengelola peralatan kantor di SMK NU 01 Kendal baik secara simultan maupun parsial.Populasi dalam penelitian ini adalah siswa kelas X jurusan administrasi perkantoran sebanyak 94siswa.Metode pengumpulan data yang digunakan adalah metode kuesioner dan dokumentasi.Teknik analisis data menggunakan analisis deskriptif persentase, analisis regresi linier berganda, analisis uji asumsi klasik, dan analisis uji hipotesis.Analisis regresi berganda menunjukkan bahwa ada pengaruh motivasi belajar, disiplin belajar dan media pembelajaran terhadap kesiapan belajar siswa kelas X administrasi perkantoran pada mata diklat mengelola peralatan kantor di SMK NU 01 Kendal baik secara simultan maupun parsial.  Preparation to studyis the basic need that must be done by students Office Equipment learning outcomes. Learning readiness can be influenced by learning motivation, learning discipline and learning media. The problem of this study:Was there are any influence of learning motivation, learning discipline and learning media toward the 10th grade students’ learning readiness of OfficeAdministration in managing Office Equipment in SMK NU 01 Kendal. The population were 10thgrade student of Office Administration at SMK NU 01 Kendal, they were 94 students. The data were collected by questiononaires and documentation. The data were analyzed by percentage desciptive analiysis, multiple linear regression analysis, analysis classical assumption test, hypothesis testing and SPSS analysis. The results of multiple linear regression analysis showed that the equation Y = 7.472 + 0.163X1 + 0.155X2+ 0.369X3, with F test was obtained F =  16.278 with a significance 0.000 and less than 0.05. Simultaneously, the influence of learning motivation, learning discipline and learning media toward the 10th grade students’ learning readiness was35.2%. Partially, the influence of learning resources toward the 10th grade students’ learning motivation was4.45%, 5.71% and the learning discipline and influence of learning media 6.35%.